Sosialisasi Dan Pendampingan UMKM Dalam Pembuatan NIB Melalui Sistem Online Single Submission (OSS) Di Kampung Pasir Banteng Desa Cihanjawar Kabupaten Purwakarta - Sari Lestari; Hamdan Ardiansyah (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) must take care of and are required to have a business license as proof of the legality of the MSMEs they have established are recorded and have a license to operate.  One of the business legalities that must be owned by business actors is the Business Identification Number (NIB). NIB is defined as an identification for business actors, both individually owned and non-individual-owned businesses. However, in its implementation, not all MSMEs understand the importance of the legality of the business. In addition, many MSMEs do not know how to make the NIB legality. Based on observations that have been made, no MSMEs in Pasir Banteng have NIB. One of the contributing factors is the lack of public understanding of the importance of doing business registration, and the public does not know how to take care of business registration to get NIB. Based on these problems, it is necessary to socialize and assist in making NIB through the Online Single Submission (OSS) system. The stages carried out are by conducting surveys and obses, socialization, assistance in making NIB, and handing over NIB to MSMEs. The result obtained from this service is an increase in public understanding of the importance of having business legality and the community understands how to make it.